Pensamiento crítico como lo vive un estudiante: un acercamiento fenomenológico (2020)
Nowadays, the goal of teaching students to think critically seems ubiquitous in educational discourses worldwide. It is often said that if students develop this kind of thinking, they will be able to participate more aptly in social and democratic life because they could examine their thoughts and reasons and thus make better decisions. Such discourse has given rise to countless studies on the critical thinking levels of students and teachers in various areas of knowledge. On the contrary, little has been investigated regarding the very experience of thinking critically, that is, a phenomenological research about what a person experiences while exercising critical thinking. To respond to this lack of investigation, this article intends to present a phenomenological-hermeneutic description of the critical thinking experience developed as part of a phenomenological research. The relevant question in this paper is how do students experience critical thinking?